Spatial and temporal evolutions of terrestrial vegetation drought and the influence of atmospheric circulation factors across the Mainland China - Fei Wang; Hexin Lai; Ruyi Men; Ke Sun; Yanbin Li; Kai Feng; Qingqing Tian; Wenxian Guo; Xuefang Du; Yanping Qu (Ecological Indicators, 2024)
Vegetation drought can reduce the net ecosystem productivity, resulting in disturbances to the sustainable development of humans and nature. In this study, Vegetation Health Index (VHI) was used to identify vegetation drought. The spatial and temporal evolution of vegetation drought was characterized using the Pixel-based Trend Identification Method (PTIM) in China from 1982 to 2020. Moreover, multiple cross-wavelet techniques were used for revealing the correlations between atmospheric circulation factors and their combinations with vegetation drought. The results indicates that: (1) there is a decreasing trend of vegetation drought in China during the study period, while it will show an increasing trend in the future; (2) the South China is prone to spring drought and summer drought, and the Sichuan Basin is prone to autumn drought and winter drought; (3) in spring, the most obvious trend of vegetation drought mitigation appears; (4) a combination of atmospheric circulation factors, North Pacific Index (NPI)-North Atlantic Oscillation (NAO)-Arctic Oscillation (AO), has the most significant impact on vegetation drought across China.